Chemokine receptors on peripheral blood T lymphocytes in children on peritoneal dialysis. Issue 2 (March 2021) - Szczepańska, Maria; Sędek, Łukasz; Bulsa, Joanna; Mazur, Bogdan; Zwolińska, Danuta; Tkaczyk, Marcin; Karpe, Jacek; Szczepański, Tomasz
Background: Immune cell dysfunction is listed among complications resulting from chronic kidney disease (CKD). It could be associated with T-cells, which play a role in the lymphocytic migration and infiltration. However, the data on chemokine receptors expression on T-cells in patients with CKD particularly treated with peritoneal dialysis (PD) are still limited. Methods: The study aimed at multiparameter flow-cytometric analysis of the absolute numbers and percentage of T-cell subsets with surface chemokine receptors (CCR4, CCR5, CCR7, CXCR3, and CXCR4) or receptors' combinations in 47 children treated with PD. Results: We found lower absolute numbers of total T lymphocytes, lymphocytes with surface CCR5, CXCR4 + CCR5, CXCR3 + CCR5 antigens and T-cells with CCR4, CCR4 + CD4, CXCR3, CXCR3 + CD4, and CD8 receptors. Lymphocytes T with CD4, CCR7, CD28 + CCR7, CXCR3 + CD8 antigens showed higher percentage in children on PD as compared to healthy children and opposite percentage values of CCR4 +, CCR4 + CD4 +, CXCR3 + T lymphocytes were diminished. Mean fluorescent intensity for CCR7 +, CCR7 + CD45RO +, CCR7 + CD28 +, CXCR4 + CD4 +, CCR5 + CD4 +, CCR4 +, CCR4 + CD4 + T-cells was lower in the PD group than in healthy children. The analysis of correlation between T lymphocyte subpopulations with chemokine receptors and other parameters revealed positive correlation of CCR7 + and CCR7 + CD28 + T-cells and weekly creatinine clearance, negative correlation between the percentage of CD45RO + CCR7 antigen positive T-cells and KT/Vurea . Summary: In conclusion, we could not confirm the phenomenon of earlier senescence of T-cells in children with CKD on PD treatment. This still requires further investigation. The higher percentage of T-cells with CCR7 surface receptor could be responsible for the increase of proliferation activity in this group of children.